Driving simulator study of text messaging and phone conversations: Effects of messages’ valence, drivers’ values and self-reported driving behaviors - Ivars Austers; Inese Muzikante; Ronalds Cinks (Heliyon)
This study investigated the impact of reading emotionally-laden text messages and engaging in handheld phone conversations on driving behavior in a simulated environment. Additionally, the study explored how driving behavior correlates with individual differences in basic human values and self-reported risky driving patterns (e.g., violations, errors, and lapses). A within-subject design was employed, where all participants read both a negative and a positive text message and answered a phone call while driving in the simulator. Results showed that average driving speed remained unchanged after receiving text messages and during phone calls but increased after the call ended. However, the standard deviation of speed varied across different conditions. Regarding centerline deviation, participants maintained a consistent distance from the centerline during baseline driving and after reading text messages, but moved closer to the centerline during phone conversations. Self-reported values of power, security, and universalism were significantly correlated with objective driving measures: power was associated with riskier driving behaviors, whereas security and universalism were linked to safer driving patterns. Moreover, self-reported driving errors and lapses were positively correlated with increased driving speed during and after phone calls.